Squamous cell carcinoma of conjunctive with local invasion - Pedra Rodríguez Montero; Yunia Toledo Rodríguez; Santos Álvarez Yero (Centro Provincial de Información de Ciencias Médicas, 2019)
The case report of a 62 years mestiza patient of rural origin is presented, who had been assisted 3 years ago in the ophthalmology service due to a tumor of conjunctive in the left eye. She went again to the service for this reason, but this time it also existed profuse bleeding and serious damage of the ocular structures. Several exams were carried out, among them orbit X rays, ocular echography, orbit and skull tomographies (with contrast), as well as biopsy of the exofitic lesion and immunohistochemical study. The definitive histologic diagnosis was squamous cell carcinoma of conjunctive, reason why it was decided to carry out orbit exeresis, reconstructive cosmetic surgery and, later on, radiotherapy and chemotherapy. The patient had a favorable clinical course and the dissemination of the malignancies was controlled, what could also be avoided if initial medical care might have been opportune.